Republic of Tajikistan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper analyzes the sources of recent growth in Tajikistan. It concludes that economic growth has been mainly driven by the services sector and a surge in remittances that have been mainly used for private consumption and small-scale private investment. The paper summarizes the recently introduced revisions to the Tax Code, which are an evolutionary step in simplifying the tax system and setting the base for better revenue administration. It also examines the likely impact on households of increasing electricity prices to cost-recovery levels.